2001
DOI: 10.1210/jcem.86.10.7889
|View full text |Cite
|
Sign up to set email alerts
|

The CAG Repeat Polymorphism in the AR Gene Affects High Density Lipoprotein Cholesterol and Arterial Vasoreactivity

Abstract: Genomic effects of T are exerted via the AR. The length of the polymorphic CAG repeat sequence in the AR gene is inversely correlated with the transcriptional regulation of target genes by T. In 110 healthy men (20-50 yr), we investigated the interactions among this polymorphism, serum levels of sex hormones, cardiovascular risk factors, and flow-mediated and nitrate-induced vasodilatation of the brachial artery. The number of CAG repeat had no significant correlations with serum concentrations of total or fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
72
6
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 70 publications
15
72
6
4
Order By: Relevance
“…Since the amount of blood drawn was restricted to 60 ml, multiple determinants were assessed and serum was scarce, complete parameters including leptin, insulin and c-peptide concentrations were assesssed in 106 volunteers. Other results of this study have been published previously [38,39].…”
Section: Methodssupporting
confidence: 62%
See 2 more Smart Citations
“…Since the amount of blood drawn was restricted to 60 ml, multiple determinants were assessed and serum was scarce, complete parameters including leptin, insulin and c-peptide concentrations were assesssed in 106 volunteers. Other results of this study have been published previously [38,39].…”
Section: Methodssupporting
confidence: 62%
“…By its attenuating influence on androgenicity, a high number of CAGr exerts adverse effects on fat mass and insulin sensitivity and thereby also on cardiovascular risk. Simultaneously, however, testosterone and a low number of CAGr in the AR gene decrease HDL-cholesterol via direct effects on pivotal genes of HDL metabolism as well as on endothelium-dependent and independent vasoreactivity [39]. Therefore, similar to testosterone, the CAGr polymorphism in the AR gene seems to play an ambiguous role in the determination of atheroclerotic risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which hyperandrogenemia might affect endothelial function are complex and controversial. It is possible that testosterone has a direct effect on the vessel wall, as indicated by the localization of androgen receptor (AR) in endothelial and vascular smooth muscle cells [28], influencing vasodilatation by endothelium-dependent and endothelium-independent mechanisms, by genomic and non-genomic effects [29,30]. Zitzmann et al observed that the number of CAG repeats in the AR gene showed a significant positive basic correlation with FMD, GTN-induced vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
“…A control group composed of 32 women (age: 23.06 ±5.37 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), BMI: 25.87± 6.89 (16.88-42.86) kg/m 2 ) was selected as to be similar to the group of patients in terms of age and BMI. In the end though, our intention was not fully accomplished because there was still a significant difference in BMI between the groups.…”
Section: Study Protocolmentioning
confidence: 99%